Robots, intentionality and artificial intelligence - Teixeira, João de Fernandes (1991)
The paper focuses in philosophical problems concerning the nature of intentionality and mental representation. The first part presents a historical outline of the problem and reviews some classical/contemporary writings on the question. The second part examines the so-called Chinese Room Argument formulated by J. Searle. The third part presents a few arguments aiming to show the inadequacy of the functionalist model for the design of robots. The conclusion points to some alternatives to the traditional functionalist model such as, for instance, the connectionist model.